2012
DOI: 10.1016/j.dsp.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficient frequency estimation of a single real tone based on principal singular value decomposition

Abstract: The problem of single-tone frequency estimation for a discrete-time real sinusoid in white Gaussian noise is addressed. We first show that the frequency information is embedded in the principal singular vectors of a matrix which stores the observed data with no repeated entry. The technique of weighted least squares is then utilized for finding the frequency from the singular vectors. It is proved that the variance of the frequency estimate approaches Cramér-Rao lower bound when the data observation length ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In this paper, we considered the estimation of frequencies of a superimposed exponential signal model. We generalized the PUMA method [13][14][15][16] from sinusoids with additive noise to multiple signals with multiplicative and additive noise. The techniques SVD and WLS are used to obtain the frequency estimation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this paper, we considered the estimation of frequencies of a superimposed exponential signal model. We generalized the PUMA method [13][14][15][16] from sinusoids with additive noise to multiple signals with multiplicative and additive noise. The techniques SVD and WLS are used to obtain the frequency estimation.…”
Section: Discussionmentioning
confidence: 99%
“…It can be observed that the frequency information is contained in G and H but the frequency estimation is not directly available from { ( )} y t . In this paper, we use the PUMA method [13][14][15][16] for frequency estimation as follows.…”
Section: Proposed Frequency Estimation Methodsmentioning
confidence: 99%
See 3 more Smart Citations